2006
DOI: 10.1086/499304
|View full text |Cite
|
Sign up to set email alerts
|

SDSS J103913.70+533029.7: A Super Star Cluster in the Outskirts of a Galaxy Merger

Abstract: We describe the serendipitous discovery in the spectroscopic data of the Sloan Digital Sky Survey of a starlike object, SDSS J103913.70+533029.7, at a heliocentric radial velocity of +1012 km s À1 . Its proximity in position and velocity to the spiral galaxy NGC 3310 suggests an association with the galaxy. At this distance, SDSS J103913.70+533029.7 has the luminosity of a super star cluster and a projected distance of 17 kpc from NGC 3310. Its spectroscopic and photometric properties imply a mass of >10 6 M a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
3
2
0
Order By: Relevance
“…It appears clear that the knots discovered here strongly support the second scenario, suggesting that at least part of the population of ultracompact dwarfs originate from young massive star clusters: we are probably for the first time witnessing the dawn of the UCDs. This scenario is also consistent with the recent discovery of a massive extragalactic star cluster ( M ≥ 10 6 M ⊙ , t ≈ 700 Myr) lying at a projected distance of 17 kpc from the merger remnant NGC 3310 and likely formed during the merging event (Knapp et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…It appears clear that the knots discovered here strongly support the second scenario, suggesting that at least part of the population of ultracompact dwarfs originate from young massive star clusters: we are probably for the first time witnessing the dawn of the UCDs. This scenario is also consistent with the recent discovery of a massive extragalactic star cluster ( M ≥ 10 6 M ⊙ , t ≈ 700 Myr) lying at a projected distance of 17 kpc from the merger remnant NGC 3310 and likely formed during the merging event (Knapp et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…It appears clear that the knots discovered here strongly support the second scenario, suggesting that at least part of the population of ultra-compact dwarfs originate from young massive star clusters: we are probably for the first time witnessing the dawn of the UCDs. This scenario is also consistent with the recent discovery of a massive extra galactic star cluster (M 10 6 M⊙, t ≈ 700 Myr) lying at a projected distance of 17 kpc from the merger remnant NGC3310 and likely formed during the merging event (Knapp et al 2006). Finally the diffuse stellar streams and ionized gas observed along the trails suggest that the mechanisms acting here will significantly influence the properties of the intracluster light and contribute to the enrichment of the ICM.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the debris is consistent with a small burst of star formation in the past 50 Myr, (which is consistent with the ages of the young stellar clusters in the central starbursting region; de Grijs et al 2003a), and recent work by Knapp et al (2006) suggests that a secondary star formation event, as indicated by the presence of a young stellar cluster, may have occurred in this system approximately 750 Myr ago. This discrepancy may result from either unique, sequential mergers with NGC 3310, or the incoming companion and its resulting debris completing multiple orbits before finally being destroyed.…”
Section: Discussionsupporting
confidence: 79%